Differences in Sleep Quality of Schizophrenia Patients Based on Gender at Madani Hospital Medan, North Sumatra - Zulhilmi, Zulhilmi; Nuralita, Nanda Sari; Rizaldi, Aril; Asfur, Robitah (Buletin Farmatera, 2024)
Abstract: Schizophrenia is a severe mental disorder, this disorder is characterized by delusions, hallucinations, thought disorder, restlessness, strange or hostile behaviour, feeling (affect) dull or flat, interest away from social interactions, little emotional contact (quiet, difficult to talk to), passive, apathetic or indifferent, difficult to think abstractly and lose of motivation. Sleep disturbances have been assessed in various studies in patients with schizophrenia, using subjective (ie daily interviews, sleep diaries) and objective (ie, polysomnography and actigraphy) parameters. Compared with healthy controls, patients with schizophrenia exhibit longer sleep onset latency, decreased sleep efficiency, more nighttime awakenings, increased daytime dysfunction due to sleep deprivation, poorer overall sleep quality, and a higher proportion of sleep disturbances. Previous studies have suggested that poor sleep quality is associated with female gender in schizophrenic patients. This study aims to determine the difference in sleep quality of schizophrenia patients based on gender at Madani Hospital Medan, North Sumatra. This study is an analytical descriptive with a cross-sectional study approach, sampling method using a purposive sampling technique. The data of this study were obtained from primary data using questionnaire instruments and patient medical records. Data analysis using Chi-Square test. The results showed that the sleep quality of male research respondents with disturbed sleep quality was found in 18 people (51.4%), and undisturbed sleep quality was found in 17 people (48.6%). Of female research respondents, 22 people (62.9%) had disturbed sleep quality and 13 people (37.1%). The p-value was found to be 0.334 (p0.05), which means that there was no significant difference in the sleep quality of schizophrenic patients based on gender at Madani Hospital Medan, North Sumatra. There was no significant difference in the sleep quality of schizophrenic patients based on gender at Madani Hospital Medan, North Sumatra.